Genetic diversity in section Rhizomatosae of the genus Arachis (Fabaceae) based on microsatellite markers - Angelici, Carla M. L. C. D. [UNESP]; Hoshino, Andrea Akemi [UNESP]; Nóbile, Paula Macedo [UNESP]; Palmieri, Darío Abel [UNESP]; Valls, José F. Montenegro; Gimenes, Marcos A.; Lopes, Catalina Romero [UNESP] (Sociedade Brasileira de Genética, 2008)
The genus Arachis (Fabaceae) native to South America, contains 80 species divided into nine sections, three of which contain species of special economic importance such as the cultivated peanut (Arachis hypogaea), belonging to the section Arachis, and some perennial forage species from sections Caulorrhizae and Rhizomatosae. We used microsatellite markers to assay genetic variability among 77 accessions of four species from section Rhizomatosae, the diploid Arachis burkartii (2n = 2x = 20) and the tetraploid Arachis glabrata, Arachis pseudovillosa and Arachis nitida (2n = 4x = 40). A total of 249 alleles were found in the fifteen loci analyzed and a high degree of intra and interspecific polymorphism was detected. The lowest intraspecific variation occurred in Arachis burkartii, while the smallest estimated interspecific value was between A. nitida and A. pseudovillosa and the largest was between A. burkartii and A. nitida. High observed heterozygosity was detected in A. glabrata. The diploid accessions grouped in one cluster and the tetraploid accessions in another. It was possible to distinguish all 77 accessions and the genetic distance between accessions could not be correlated with geographic origin.
Keywords: Arachis; genetic diversity; microsatellite; peanut; Rhizomatosae